Students’ Problems in Paraphrasing The Text at Halu Oleo University - Rezkilaturahmi, Rezkilaturahmi; Hanna, Hanna; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2021)
Paraphrasing is one of the major skill for academic writing and some have considered that the teaching of paraphrasing can help students avoid copying from source texts. The objective of this research was to find out the problems faced in paraphrasing the text and how to deal with the problems. Quantitative design was used in this study to answer the research questions. There were 10 participants as the subject in this study. The data were collected from paraphrasing text, questionnaire, and interview. The finding of the data analysis shows that lack of vocabulary and lack of grammar knowledge are the problems faced by most of the participants in paraphrasing the text. From the text, it was found that just 17% of students were able to change the word or synonym from the original text and 17 % students were able to change grammar or structure from original text. From the questionnaires, the means score shows that the students have most problems in grammar and lack of vocabulary in paraphrasing the text in which the highest means score fall into the question 17 and 19 with score 3. From the interview, it was also found that most students mentioned lack of vocabulary and grammar as the problems in paraphrasing the text. Furthermore, practicing more, reading more the original text, reading the dictionary and learning more from the internet are the solutions to deal with the problems in paraphrasing the text.